The littoral sea cucumber (Echinodermata: Holothuroidea) fauna of Guam re-assessed – a diversity curve that still does not asymptote - Borrero-Perez, G.H.; M., Honey; Kamarudin, Kamarul Rahim; A., Kerr; Kim , S.; Menez, A.; Michonneau , Francois; Ochoa, J.A.; Olavides , R.D; G., Paulay; Y., Samyn; A., Setyastuti; et al. (2012)
The Micronesian island of Guam has been an important site for the study of tropical holothuroid taxonomy for almost 200 years. Despite such substantial attention by both expeditions and resident taxonomists, new records are being regularly added to the fauna demonstrating the challenge of documenting the biota of even a small hyper-diverse area. Guam is the type locality of species described by Quoy & Gaimard (1833) and Brandt (1835). A survey of the sea cucumber fauna by Rowe & Doty (1977) led to one of the most used guides for the identification of tropical Pacific sea cucumbers because of the color illustrations of living animals it presented. Focus on echinoderms including holothuroids continued with numerous new records added in the following decades. Paulay (2003) summarized the fauna last, recording 46 species, including 9 new records. At this stage the fauna was thought to be well documented. A week-long workshop on holothuroid systematics sponsered by the NSF PEET project in 2010 included a substantial field work component, sampling both during the day and night, with snorkeling and SCUBA, across a variety of habitats, yielding more than 40 species. 10 of these proved new records for Guam; two proved new to science. Further sampling by Kerr’s lab since the workshop has added two additional species. The holothuroid fauna of Guam thus now comprises 58 species that belong to 17 genera and 7 families. This contribution presents them as an illustrated and briefly annotated checklist.